Relational Contracts and Supplier Turnover in the Global Economy - Christian Fischer; Jens Suedekum; Fabrice Defever (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Headquarters and their specialized component suppliers have a vital interest in establishing long-term collaborations. When formal contracts are not enforceable, such efficiency-enhancing cooperations can be established via informal agreements, but relational contracts have been largely ignored in the literature on the international organization of value chains. In this paper, we develop a dynamic property rights model of global sourcing. A domestic headquarter collaborates with a foreign input supplier and makes two decisions in every period: i) whether to engage in a costly search for a better partner, and ii) whether to make a non-binding offer to overcome hold-up problems. Our key result is that the possibility to switch partners crucially affects the contractual nature of buyer-supplier relationships. In particular, some patient firms do not immediately establish a relational contract, but only when they decide to stop searching and thus launch a long-term collaboration with their supplier. From our model, we develop an instrumental variable estimation strategy that we apply using transaction-level data of fresh Chinese exporters to the US. We obtain empirical evidence in line with the theoretical prediction of a positive causal effect of match durations on relational contracting.
Keywords: F23; D23; L23; 330